(untitled) (Eurasian Journal of Ecology, 2018)
Prospects for using vegetable beans for breeding and food production One of the most prospective strategies of agricultural policy in the Republic of Kazakhstan at present is manufacturing effective competitive agricultural production and supply with quality food products. Major role in this direction belongs to growing sowing areas of legumes, and common in particular. Common bean is one of basic vegetable crops of high economic value in different countries. Out of all legumes common bean has high nutritional value and may be used for different nutritional aims. In human daily ration in many countries common bean is the resource of proteins, essential and non-essential amino-acids, micro and macro elements and vitamins. In modern world the breeding of vegetable bean should be targeted to generation of new, prospective varieties on the basis of complex assessment of domestic and foreign genotypes by implying marker selection and introduction new technologies. Main biological and morphological characteristics of vegetable beans, i.e. agronomical and food values, are highlighted in this article. There are the key principles and modern research in the field of the legumes breeding which are accepted in different countries. Analysis of literature sources of Russian and foreign authors over the past 10-15 years has demonstrated that breeding of vegetable beans should be concentrated on complex assessment of specimens in accord with such traits as productivity, resistance to stress factors and increased nutritional value. To assess productivity it is necessary to take into account that the modern varieties of common beans have high biological and physiological difference across populations, i.e. the presence of biotypes with low, medium and high potential of the traits. One of the ways towards increased productivity is providing experiments on optimizing biotic structure of populations. Currently these investigations are conducted by conventional and molecular genetic methods. Introduction of marker selection on the basis of DNA-markers will promote the development of new, prospective varieties with economically valuable characteristics and disease resistance for agricultural harvesting. This article provides main directions of the use of marker selection to determine specimens and varieties which are resistant to drought, viral and fungal diseases, the study and the assessment of genetic diversity of common bean genotypes. Principal investigations on cultivation of varieties with increased nutritional value is aimed at improving quality and quantity composition of proteins, balanced in amino acids, enriched with microelements and vitamins and possessing low amount of antinutrients. These varieties will allow to meet the needs of food industry in legumes and make vegetable beans more widespread. Special attention is paid to the prospects of cultivation of vegetable beans in Kazakhstan. It has been shown, that the expansion of cultivation areas is quite profitable having high economic importance for our Republic. The introduction of the beans into agricultural production will assist in increasing the profitability of the farms, to develop new branches of food industry, provide plant products with high protein content of the to the population of our Republic and improve people,s health and wealth. Key words: vegetable beans, cultivar, breeding, food industry.